Characteristics of adolescent athletes with pain during sports activities: evaluation of flexibility using ultrasound elastography - Hiroaki Kijima; Masashi Fujii; Tetsuya Kawano; Hidetomo Saito; Naohisa Miyakoshi (Japanese Society of Physical Fitness and Sports Medicine, 2023)
Medical checkups for adolescent athletes aim to prevent or detect sports injuries and manage them before they hamper future sports activities and daily life. However, effective items for evaluation, as well as the areas of intervention to prevent sports injuries, remain unclear. We aimed to clarify the checkup items and intervention areas to prevent sports injuries in adolescent athletes. This is a cross-sectional observational study that investigated the presence or absence of pain in adolescent athletes and associated factors at the time of checkup. We investigated joint laxity, range of motion (ROM), finger-floor distance (FFD), heel-buttock distance (HBD), straight leg raising (SLR) angle, too many toes sign, and presence or absence of low back pain during lumbar extension in 301 junior high school athletes. Additionally, after confirming the developmental stage of the tibial tuberosity using ultrasonography, ultrasound elastography was used to quantify the elasticity of the quadriceps femoris, and items related to pain during sports activities were extracted. Items related to pain included the too many toes sign, low back pain during lumbar extension, and elasticity of the quadriceps femoris. Athletes with a positive too many toes sign were less likely to experience pain; conversely, the harder the quadriceps femoris, the more likely they were to experience pain. Medical checkups focusing on these items are effective for adolescent athletes who are prone to knee pain.